(untitled) (Research, Society and Development, 2025)
Introduction: Preoperative fasting is a practice used to reduce gastric contents, minimizing the risks of regurgitation and pulmonary aspiration. Among the clinical outcomes associated with prolonged fasting are dehydration, electrolyte imbalance, and hypotension during anesthetic induction. Fasting abbreviation (FA) is an essential care protocol for patients undergoing elective surgeries. Objective: To describe the care protocol for fasting abbreviation based on the digitalization of preoperative care processes. Method: This ecological, descriptive, retrospective study was conducted in a public hospital in the city of São Paulo. Data related to the FA indicator were measured from 09/01/2024 to 09/30/2025, based on elective surgery cases. Descriptive analysis was performed at the end of data collection. Results: Among the surgical procedures performed, cholecystectomies were the most prevalent (35%), followed by hernia repair surgeries (19%), gynecological procedures (15%), orthopedic surgeries (12%), other procedures (11%), and pediatric surgeries (8%). Regarding sex, females predominated (62%) compared to males (38%). Adherence to the abbreviated fasting protocol showed a gradual increase and stable maintenance throughout elective surgery cases. Conclusion: Adherence to the FA protocol demonstrated compliance with institutional targets, with sustained results over the analyzed period. The use of digital tools strengthens nursing care management by integrating and consolidating clinical information, resulting in improved quality and patient safety for users of the Brazilian Unified Health System (SUS).